Effect of mode of delivery on incidence of retinopathy of prematurity: a systematic review and meta-analysis - Vera Sumual; Reynardi Larope Sutanto; Angelina Patricia Chandra (BMJ Open Ophthalmology)
Background Retinopathy of prematurity (ROP) is a leading cause of childhood blindness worldwide. Prompt diagnosis and treatment are crucial in ROP management. Thus, the identification of prominent risk factors could facilitate immediate action. Among various risk factors, the effects of mode of delivery on ROP remain unclear. Therefore, this study aims to assess the association between different modes of delivery on ROP incidence.Methods and analysis Comprehensive literature search was conducted on PubMed, ProQuest, EBSCOHost and Cochrane databases, to evaluate the association of mode of delivery—vaginal delivery or caesarean section (c-section)—and the incidence of ROP from inception to December 2023. Random-effects meta-analysis was performed to estimate the pooled OR along with their 95% CIs.Results This review included 5 cohort studies involving 2048 babies. A higher incidence of ROP was observed in infants born through vaginal delivery compared with caesarean section. Meta-analysis showed that C-section decreased the unadjusted odds of having ROP infants by 46% with low heterogeneity (OR 0.54 (95% CI 0.40 to 0.73); I2=40.73%). However, pooled adjusted effects were statistically insignificant with moderate heterogeneity (adjusted OR 0.59 (95% CI 0.28 to 1.23); I2=70.51%), possibly stemming from multiple variations in the controlled variables of each study.Conclusion Despite varying statistical significance, our findings underscore the crucial need to comprehend the influence of delivery mode on neonatal ophthalmic outcomes. Due to a limited number of existing studies, further research is needed to confirm the association.PROSPERO registration number CRD42023486278.